Annealing-induced changes in the nature of point defects in sublimation-grown cubic silicon carbide - Schöler, Michael; Brecht, Clemens; Wellmann, Peter (Materials, 2019)
In recent years, cubic silicon carbide (3C-SiC) has gained increasing interest as semiconductor material for energy saving and optoelectronic applications, such as intermediate-band solar cells, photoelectrochemical water splitting, and quantum key distribution, just to name a few. All these applications critically depend on further understanding of defect behavior at the atomic level and the possibility to actively control distinct defects. In this work, dopants as well as intrinsic defects were introduced into the 3C-SiC material in situ during sublimation growth. A series of isochronal temperature treatments were performed in order to investigate the temperature-dependent annealing behavior of point defects. The material was analyzed by temperature-dependent photoluminescence (PL) measurements. In our study, we found a variation in the overall PL intensity which can be considered as an indication of annealing-induced changes in structure, composition or concentration of point defects. Moreover, a number of dopant-related as well as intrinsic defects were identified. Among these defects, there were strong indications for the presence of the negatively charged nitrogen vacancy complex (NC-VSi)-, which is considered a promising candidate for spin qubits.
CRIS-Team Scopus Importer:2019-08-23
Keywords: 3C-SiC; Defect engineering; Doping; Photoluminescence; Point defects; Sublimation growth